Pengaruh Bauran pemasaran Jasa Terhadap Keputusan Berkunjung Wisatawan Pantai Kerang Mas Kabupaten Lampung Timur - Suprayogi, Rahmat; Sugiono, Arif; Adistya, Diang (Jurusan Administrasi Bisnis, FISIP, Universitas Lampung, 2023)
This study aims to determine the magnitude of the influence of product, price, place, promotion, people, process, and physical evidence on the decision to visit tourists visiting the Kerang Mas Beach Tourism object, East Lampung district. This type of research is an explanation with a quantitative approach. The population in this study were tourists who visited the Kerang Mas Beach tourist attraction. The sampling technique used purposive sampling with a sample of 100 respondents. The data was obtained from a questionnaire using a Likert scale. The data analysis of this research used multiple linear regression statistical analysis. The results of the study explain partially. product, price, place, promotion, people, and physical evidence have a positive and significant effect on the decision to visit. Simultaneously, product, price, place, promotion, people, process, and physical evidence of the decision to visit. The implication of this research is that the manager of Kerang Mas Beach increases promotions in order to increase the number of tourists who come. The manager of Kerang Mas Beach must also improve, add existing supporting facilities so that visitors are more comfortable in making their visit.